The Features of SEZs Functioning in the New Countries of the European Union: Experience for Ukraine (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The article analyzes the experience of new EU countries for the establishment and operation of various types of special economic zones and taxation features in these countries and in the companies in these areas of the country depending on the activity. The necessity of implementing such practices in Ukraine under the strict international supervision by creditors of our country is proved.Both positive and negative experience of SEZs applying is accumulated in Bulgaria. In particular, due to the adoption of more stringent rules in relation to excisable goods in SEZs of this country (to alcohol and tobacco products, petroleum products) the number of clients of Rousse area has gradually reduced. Therefore, we believe that it’s inappropriate to provide benefits for excisable goods while creation of special economic zones in Ukraine.Restoration of special economic zones in Ukraine will solve the problem of accelerated development of the insufficient developed regions of our country, as it was evidenced by the experience of Poland. Most of the foreign direct investments of the world's leading corporations coming to Poland are directed to the manufacturing sector, it is placed in these areas.The benefits to enterprises in FEZs of Lithuania allowed to reduce unemployment in the country and to stop migration from the country, which is very important for Ukraine today.FEZ of Latvia have fulfilled their tasks, with the exception of Rezekne FEZ, that was connected with the loss of the Russian market by the enterprises of this area and the lack of skilled labor because of their emigration to more developed EU countries. Ukraine and Volyn can face the similar phenomenon in creating FEZ, since many residents of border regions are advantageous to smuggle than to work for domestic enterprises.The feature of free economic zones management in Estonia is that they are managed by the owners of SEZs, it is important to consider in Ukraine. The country is also attractive for reinvestment of capital, as in Estonia, there is a tax rate of 0 % on retained earnings.
Keywords: European Union, special economic zones, free economic zones, free trade zones, Bulgaria, Poland, Lithuania, Latvia, Estonia, retained earnings